'From there to here': narratives of transition, migration and national identity in Irish media representations of rugby union in the professional era. Issue 3 (3rd July 2017) - Free, Marcus
Abstract: Irish media representation of rugby union in the post-1995 professional era has become a vehicle for the rehearsal of fantasies and anxieties concerning national identity in the context of the Republic of Ireland as a neoliberal state. Irish rugby's reorganization and competitive successes have generated comforting images and discourses of centralized management, national cohesion and continuity while successive Irish governments' neoliberal policies have focused on deregulation, facilitating foreign direct investment and reduced social services spending. Representations of advancements in management intersected with pervasive managerialist discourses in Irish media and politics during and following the 2008 collapse of the Celtic Tiger boom, but with a heavy stress on serving the 'national interest'. Relatedly, the targeted import of foreign players and coaches is often depicted as reflective of Irish rugby management's successful negotiation of the neoliberal environment of contemporary European and world rugby. However, concerns regarding the potential hindrance of 'native' player/coach development and the threat of economically driven out-migration evince anxieties concerning Irish rugby's fragile economy and cultural identity that interconnect with broader concerns regarding Ireland's enduring economic vulnerability following the 2008 financial crisis.